Factors affecting trust in publishing personal information in online social network: An empirical study of Malaysia’s Klang Valley users - Syed Shah Alam,; Maisarah Ahmad,; A. Ali Khatibi,; Mst. Nilufar Ahsan, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Online Social Networking (OSN) is a platform that enables one to socialize over the world online without having to meet anyone physically or face to face. However, privacy in OSN sites is becoming a main concern for users because of the potential threats that come with sharing one’s personal information online. The purpose of our study was to examine the key factors that influence the trust in publishing personal information on Online Social Network (OSN) sites in Malaysia. Primary data were gathered from 201 users comprising university students and working adults residing in the Klang Valley. Five factors were selected to gauge the users’ perception of potential threats , namely, security/privacy of the website, word of mouth of family and friends, functional motives of OSN users, social motives of OSN users and psychological motives of OSN users. Results of the study showed that security/privacy, word of mouth, functional motives and social motives significantly affected the publishing of respondents’ personal information on online social network sites. The implication is that the largest challenge of both now and in the future, in terms of users protecting themselves and their information, will be to find out and understand how to effectively access and change the privacy settings offered by all OSN sites.